ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Ramadhan Sukma Perdana; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
Financial crisis in many countries as a result of weak good corporate governance practices, have focused  attention  on  the  importance  of  good  corporate  governance. Application of corporate  governance  by  companies  with  the  objective  of creating management good  management  and  accountability  for  the  company's credibility that is expected to enhance firm value. This study aimed to analyze the effect of  the application of mechanism corporate governance on firm value. The population of this study is banking companies listed in Indonesian Stock Exchange (IDX) in 2010-2012. The total study observations was 78. Results of this study showed that institutional ownership no significant effect to firm value. Second, audit committee no significant effect to firm value. Third, external auditor no significant effect to firm value. Meanwhile, there are significant effect on managerial ownership and the proportion of independent board to firm value.